Crystal Schottisch - WM. Byerly::::::::: (Firth, Pond & Co.)
Piano score, 5 p. cover title: To Theodore Sedgwick, Esq. The Crystal Schottisch cover lithograph in color of the New York Crystal Palace, by Sarony & Major